COUNTRY CASE: Micro, Small and Medium Enterprises in Vietnam - Pham Van Hong (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2017)
The definition of micro, small and medium enterprises (MSMEs) in Vietnam is stipulated in Law on Support for Small- and Medium-sized Enterprises by June 2017. As defined, MSMEs that have business registration in accordance with the Law is divided into three levels: micro, small and medium scale, basing on total capital (total capital equivalent to total assets determined in the balance sheet of enterprises) or number of employees per year, as given in Table 1.